Asuhan Kebidanan Komprehensif pada Ny S Umur 27 Tahun dengan Kekurangan Energi Kronik dan Anemia di Wilayah Kerja Puskesmas Bumiayu Tahun 2023 - Noer Syifa Noviyanti; Maryam Maryam; Khunelis Khunelis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Risk factors for pregnancy that cause complications and maternal death include chronic energy deficiency and anemia. The pregnancy rate for pregnant women with chronic energy deficiency at the Bumiayu Community Health Center in 2022 is 56 cases, while the incidence of anemia at the Bumiayu Community Health Center is 22 cases. Research method: the method used in this research is a qualitative descriptive method with a comprehensive case study approach. Comprehensive midwifery care for Mrs S found early pregnancy problems, namely chronic energy deficiency and anemia. The delivery was carried out normally vaginally and the baby was born normally. During the postpartum and birth control period, no complications were found. Comprehensive midwifery care for Mrs S with chronic energy deficiency and anemia was in accordance with midwifery care and no complications occurred.